Влияние легирования сплавов системы Co–Fe карбидами TaC, NbC и WC на их взаимодействие с графитом при нагреве под высоким давлением - Боримский, А.И.; Нагорный, П.А.; Делеви, В.Г.; Чипенко, Т.Ю.; Крикун, В.Н.; Кузьменко, Е.Ф. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
On heating up to 1600 K at a pressure of 4,8–5,0 ГПа the structures of the contact melting
zones formed during the interaction of the Co-Fe system alloys doped with TaC, NbC and WC carbides and graphite contain (irrespective of the carbide content of alloys) phases, characteristic both
of the stable (solid solution - graphite), and metastable (solid solution - Ме₃С-type carbides) states
of the alloys. The distributions of phases and sublayers in the contact melting zones correspond to a
horizontal section of the phase diagram of the Fe-C system. The sublayer, which forms on the border with graphite and contains no carbides, corresponds to the peritectic region of the diagram at
high pressure.